Cultural adaptation and psychometric validation of the academic progress goals scale for Peruvian university students - Ventura-León, José; Lino-Cruz, Cristopher; Tocto-Muñoz, Shirley; Gamboa-Melgar, Goldie; Ruiz-Castro, Jonathan (Frontiers in Education, 2025)
IntroductionAcademic goal progress is a key motivational construct linked to students' planning, self-regulation, and academic success, yet there is a dearth of culturally adapted, validated instruments for assessing this construct in Peruvian higher-education contexts. Grounded in Social Cognitive Career Theory, this study addresses this gap by adapting and validating the Academic Progress Goals Scale (AGPS) for Peruvian university students.MethodsA total of 1,157 undergraduate students (Mean Age = 21.55, SD = 4.13; 64.4% female) completed the adapted seven-item AGPS. Exploratory Factor Analysis (EFA) with WLSMV estimation and AI-based iterative optimization reduced the scale to five items. Confirmatory Factor Analysis (CFA) tested the resulting unidimensional structure. Internal consistency was estimated via McDonald's omega (ω), bootstrap resampling (1,000 draws) evaluated stability, and structural equation modeling examined convergent validity with an academic satisfaction measure.ResultsEFA supported a single factor comprising five items, with excellent fit (χ2[5] = 9.93, CFI = 0.999; RMSEA = 0.041) and reliability (ω = 0.85). The CFA confirmed this structure with near-perfect fit (χ2[5] = 3.82, CFI = 1.000; RMSEA = 0.000) and composite reliability ω = 0.85. Bootstrap analyses indicated consistently high reliability (mean ω = 0.85, SD = 0.01) and fit (CFI/TLI ≈ 1.00; RMSEA mean = 0.04). SEM revealed a moderate correlation (ϕ = 0.66) between AGPS scores and academic satisfaction, supporting convergent validity.ConclusionThe five-item AGPS is a brief, reliable, and valid tool for measuring academic goal progress among Peruvian university students. Its strong psychometric properties and cultural adaptation make it suitable for research, educational policy design, and interventions aimed at enhancing academic engagement and reducing dropout rates.